The Nordic populist radical right voters, ideology, and political interactions - Jungar, Ann-Cathrine 1962- (Routledge, Taylor & Francis Group, 2025)
"This edited volume examines populist radical right parties in the Nordic region.Somewhat surprisingly given the image of a consensual, egalitarian, and progressive region of Europe, the Nordic countries have been fertile ground for the radical right. Not only have radical right parties persisted for many decades, but they are currently much stronger in this region than in most other European countries today. In this book, the contributors analyse the electoral, ideological, and organisational aspects of the radical right in the Nordic region: The Progress Party in Norway (Fremskrittspartiet, FrP), the Sweden Democrats (Sverigedemokraterna, SD), Danish People’s Party (Dansk Folkeparti, DF), and the Finns party (Perussuomalaiset, PS). It also explores how mainstream parties and the media have reacted to the rise of the radical right, whether the radical right is integrated into mainstream politics, the extent to which they challenge the dominant ideological paradigm of Nordic politics and whether they mobilise and organise differently to other parties. Understanding the Nordic radical right is crucial to comprehending the transformation of Nordic politics but also changes in European politics more generally.This book will be of interest to students and scholars of Scandinavian politics, populism, the radical right, and comparative party politics."
Keywords: Dansk Folkeparti; Fremskrittspartiet; Perussuomalaiset; Sverigedemokraterna; Populismus; Partei; Rechtsradikalismus; Nordische Staaten; Political parties / Scandinavia; Populism / Scandinavia; Right-wing extremists / Scandinavia; Political culture / Scandinavia; Scandinavia / Politics and government / 21st century; Aufsatzsammlung